2011
DOI: 10.1007/s12072-011-9269-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury as a causal factor in mortality associated with hepatorenal syndrome

Abstract: Hepatorenal syndrome (HRS) is a form of AKI in cirrhotic patients, which is defined as a purely physiologic derangement in renal function without any effect on renal parenchyma. Recent literature challenges this understanding. Little attention is paid to the presence of renal pathology and inflammatory alterations that occur as a result of HRS and their contribution to morbidity and mortality. In this paper, we propose that any type of AKI in the presence of liver disease is an inflammatory condition. The comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…Patients were evaluated for progression to CKD after 3, 6, 12, 24, 36 and 60 months of follow up. Baseline MDRD was 72 mL/min (52–89 mL/min), at hospital discharge 51 mL/min, after 3 months 57 mL/min, after 6 months 67 mL/min (48–84), and after 12, 24, 36 and 60 months was 64 mL/min (46–81), 58 mL/min (42–79), 55 mL/min (43–76) and 53 mL/min (32–77), respectively. There was significant difference between baseline MDRD and at moments hospital discharge ( P = 0,009), after 3 months ( P = 0.03) and after 24, 36 and 60 months ( P < 0.05).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients were evaluated for progression to CKD after 3, 6, 12, 24, 36 and 60 months of follow up. Baseline MDRD was 72 mL/min (52–89 mL/min), at hospital discharge 51 mL/min, after 3 months 57 mL/min, after 6 months 67 mL/min (48–84), and after 12, 24, 36 and 60 months was 64 mL/min (46–81), 58 mL/min (42–79), 55 mL/min (43–76) and 53 mL/min (32–77), respectively. There was significant difference between baseline MDRD and at moments hospital discharge ( P = 0,009), after 3 months ( P = 0.03) and after 24, 36 and 60 months ( P < 0.05).…”
Section: Resultsmentioning
confidence: 97%
“…The patients’ characteristics are shown in Table . The age was 60.2 years (47.5 to 71), 359 were ICU patients (70.5%) and the follow‐up time was 25 months, 146 (28.7%) were diabetic, 177 (34.8%) had CKD and 192 (37.7%) had cardiovascular disease. The main aetiology of AKI was sepsis (31%).…”
Section: Resultsmentioning
confidence: 99%
“…Early adjudication between the etiologies of AKI in decompensated cirrhosis is imperative given that it has management and prognostic implications . This is especially challenging in cases of differentiating between functional AKI (HRS and PRA) and structural AKI (ATN), given that features of all three major types of AKI can be present.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the occurrence of AKI is frequent in patients with chronic liver failure and that it increases morbidity and mortality [36]. Even for patients who had received a liver transplant, a reduced GFR before the transplant was an independent predictor of mortality 30 days and 2 years after the transplantation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Even for patients who had received a liver transplant, a reduced GFR before the transplant was an independent predictor of mortality 30 days and 2 years after the transplantation [37]. Deshpande et al propose that the combination of AKI and liver failure produces a “toxic milieu” that directly causes endothelial dysfunction affecting multiple organ systems, which contributes to the increased short- and long-term mortality of these patients [36]. Our findings emphasize the catastrophic role of the interaction between chronic liver disease and AKI.…”
Section: Discussionmentioning
confidence: 99%